Forest Structure and Soil Properties in Bagale Forest Reserve, Nigeria - J. E. Omijeh; I. O. Tella (Geography, Earth Science and Environment: Research Highlights Vol. 10, 2025)
In order to study the relationship between forest structure and edaphic characteristics of Bagalle Forest Reserve an in-depth soil survey was conducted. Five fragments, Tudun Wada, Holin, Modire, Lugga and Wuro dole in altitudes, <200 m, 200-300 m, 300-400 m, 400-500 m and >750 m above sea level respectively were selected along a section line from Southwest to North-east using LANDSAT ETM +satellite imagery from Google Earth. Composite soil samples were systematically collected at four points each in the fifteen sample plots each measuring 100 by 100 meters that were laid in the fragments at 0-20 cm, and 20-40 cm depths and their physico-chemical analysis was done in the laboratory. Height, DBH, Volume, Basal area and crown area of trees in the plots were measured. Results revealed negative and positive associations between forest structure and the soil elements. Sand, texture, and bulk density had negative relationships with forest structure while clay and porosity had relatively strong positive relationships with height, DBH, Volume and Basal area. Height, DBH, Volume, Basak area and the crown area had a negative relationship with PH, EC, Phosphorus, Na, AVP, and K but positive correlations with OC, OM, TN, Ca, Mg, TEB, and TEA. Salinization is not a significant pedogenic process in the soil which also does not contain a concentration of soluble salt that may hamper the growth of plants. This reserve requires strategic interventions to ensure its long-term sustainability and development. There is a need to educate the people especially those proximal to the reserve through extension programmes and capacity building to avoid the illegal felling of trees and practice of harmful anthropogenic activities such as wrong farming techniques, and bush burning which are all detrimental to the soil and trees. This study could be used as a template to evaluate the current edaphic status and performance of trees in the forest reserves in the sub-region. This work is not conclusive and opens the window for further researches in this field.